Douglas C. Harr letter to Thomas Kent regarding notable field records for winter, February 24, 1981 - Harr, Douglas C.et al (1981)
Douglas C. Harr letter contains an annotated list of birds sighted by himself and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed